Caught in the web of the criminal justice system: autism, developmental disabilities, and sex offenses - Dubin, Lawrence; Horowitz, Emily (Jessica Kingsley Publishers, 2017)
Introduction : caught in the Web of the criminal justice system : autism, developmental disabilities, and sex offenses / Lawrence A. Dubin and Emily Horowitz -- A father's journey to protect his son : a legal perspective / Lawrence A. Dubin -- Child and juvenile pornography and Autism Spectrum Disorder / Gary Mesibov and Milissa Sreckovic -- Representing an Autism Spectrum Disorder individual charged with possession of internet child pornography : a case study / Kenneth M. Mogill -- Forensic assessment of individuals on the Autism Spectrum charged with child pornography violations / Dennis P. Sugrue -- Sex offenses, lies, and politics : the web of the registry / Emily Horowitz -- Tilting at windmills : the misplaced war on child pornography offenders / Mark H. Allenbaugh -- Egregious flaws discredit the Butner redux study : effective policies for sentencing federal child pornography offenders require findings based on valid research principles / Richard Wollert and Alexander Skelton -- Accessors and distributors of child pornography : not who you think they are / Fred S. Berlin -- Collateral damage of sex offender management policies for individuals with Asperger's syndrome and their family members / Erin Comartin -- An alternative universe : the perspective of an autistic registrant / Nick Dubin -- Navigating judicial responses for those caught in the web / Catherine Carpenter -- Asperger's syndrome and downloading child pornography : why criminal punishment is unjust and ineffective / John Douard and Pamela Schultz